2002
DOI: 10.1002/hipo.10100
|View full text |Cite
|
Sign up to set email alerts
|

Regulated transcription of the immediate‐early gene Zif268: Mechanisms and gene dosage‐dependent function in synaptic plasticity and memory formation

Abstract: ABSTRACT:The immediate-early gene Zif268 is a member of the Egr family of inducible transcription factors. Data from gene expression studies have suggested that this gene may play a critical role in initial triggering of the genetic machinery that has long been considered a necessary mechanism for maintenance of the later phases of LTP and also for the consolidation or stabilization of long-lasting memories. Until recently, however, the data supporting this assumption have been based primarily on circumstantia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
123
0
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 153 publications
(134 citation statements)
references
References 92 publications
(92 reference statements)
1
123
0
6
Order By: Relevance
“…Interestingly, in previous experiments we showed that half the complement of Zif268 in heterozygous mutant mice is not sufficient to allow the formation of a memory for the spatial location of objects as heterozygous mice are impaired in this task, however it is sufficient to form a memory of the nature of the objects [15]. Mirroring this, overexpression of Zif268 leads to enhancement of the more demanding memory for the spatial location of objects, but not to improvement of object memory over and above that observed in WT mice.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Interestingly, in previous experiments we showed that half the complement of Zif268 in heterozygous mutant mice is not sufficient to allow the formation of a memory for the spatial location of objects as heterozygous mice are impaired in this task, however it is sufficient to form a memory of the nature of the objects [15]. Mirroring this, overexpression of Zif268 leads to enhancement of the more demanding memory for the spatial location of objects, but not to improvement of object memory over and above that observed in WT mice.…”
Section: Discussionmentioning
confidence: 90%
“…To determine the effect of Zif268 overexpression on recognition memory, we first evaluated performance in an object recognition memory task using standardized procedures as previously described [1,15]. Briefly, the experimental apparatus was a black plastic square open field arena (45 Â 45 Â 30 cm) with wood shavings on the floor and a cue card placed at a fixed location on the top of one of the walls of the open field to facilitate spatial mapping.…”
Section: Zif268 Overexpression Facilitates Memory Of the Spatial Locamentioning
confidence: 99%
See 1 more Smart Citation
“…Current consolidation theory posits that a series of cellular and molecular processes within the MTL are needed during and immediately after learning to store a persistent memory trace. The formation of the trace is a dynamic process involving posttranslational protein modification and changes in gene expression (3)(4)(5)21). These events culminate in modifications in the number and strength of synaptic connections (9) that might represent the structural trace of the memory engram [reviewed by Lamprecht and LeDoux (2)].…”
Section: Discussionmentioning
confidence: 99%
“…These begin with neurotransmitter receptor activation that induces shortterm changes in synaptic efficacy based on receptor phosphorylation and trafficking (3,4). Subsequently, alterations in gene expression and protein synthesis occur that are the basis for longterm structural modifications (5,6).…”
mentioning
confidence: 99%